Análise do nível de reservas internacionais dos países emergentes de 2000 a 2010 - Gollo, Romário de Souza (Universidade do Vale do Rio dos Sinos, 2012)
Over the last 20 years, the economies have witnessed a blistering increase in their stock of international reserves. Global reserves, which were approximately one trillion dollars in 1990, went beyond two trillion dollars in 2000 and in 2010 the volume of world reserves was 9.7 trillion dollars. This process could also be observed on the MERCOSUR and BRIC countries, especially during the past five years, when the stock of reserves raised from approximately US$ 1.2 trillion at the end of 2005 to US$ 4.2 trillion at the end of 2010. In this context, the objective of this study is to analyze the level of international reserves in these countries, considering its role to reduce crisis probability and to provide credibility. The result achieved through the international reserves levels of coverage relative to short-term external debt and imports indicates that higher volumes of reserves are important to reduce the cost and the probability of crisis. Moreover, the levels of reserves accumulated by most emerging countries analyzed are above the level considered optimal. Consequently, high stock of international reserves implies unnecessary expenditures of resources for its maintenance, although they may be justified in part by the benefits they provide. For the Brazilian case in particular, the carrying cost of international reserves between 2004 and 2010 was R$ 26.8 billion a year.
Keywords: Reservas internacionais; Países emergentes; Importações; Dívida externa; Índice de cobertura; International reserves; Emerging countries; Imports; External debt; Coverage ratio; ACCNPQ::Ciências Sociais Aplicadas::Economia